Wood Pretreatment Protocols and Measurement of Tree-Ring Standards at the Oxford Radiocarbon Accelerator Unit (ORAU). Issue 2 (2014) - Staff, Richard A; Reynard, Linda; Brock, Fiona; Ramsey, Christopher Bronk
Abstract : This article presents the pretreatment protocols for wood samples processed at the Oxford Radiocarbon Accelerator Unit (ORAU), including recent implementation of a purification method to α-cellulose for non-routine samples. We examine the long-term reproducibility of measurement on wood samples at ORAU through the >1000 14 C determinations made on known-age tree-ring standards processed in each AMS wheel since our present High Voltage Engineering Europa (HVEE) AMS system came on-line in September 2002. A discussion of background measurements is also provided.